2017
DOI: 10.1155/2017/6742427
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Strategy for M2 Microglial Polarization Using Retinoic Acid-Loaded Nanoparticles

Abstract: Inflammatory mechanisms triggered by microglial cells are involved in the pathophysiology of several brain disorders, hindering repair. Herein, we propose the use of retinoic acid-loaded polymeric nanoparticles (RA-NP) as a means to modulate microglia response towards an anti-inflammatory and neuroprotective phenotype (M2). RA-NP were first confirmed to be internalized by N9 microglial cells; nanoparticles did not affect cell survival at concentrations below 100 μg/mL. Then, immunocytochemical studies were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…All these data suggest that retinoids are candidates for the treatment of neuroinflammation. Indeed, the use of RA-loaded polymeric nanoparticles (RA-NPs) modulates the murine microglial response towards an anti-inflammatory and neuroprotective phenotype (M2-like) in organotypic hippocampal slice cultures [ 143 ]. Recently, the intravenous administration of RA-NPs was shown to prevent ischemic injury in the immature brains of 2-day-old mice, demonstrating the role of RA in the control of neuroinflammation [ 144 ].…”
Section: Immunomodulatory Effect Of Ra During Inflammatory Processmentioning
confidence: 99%
“…All these data suggest that retinoids are candidates for the treatment of neuroinflammation. Indeed, the use of RA-loaded polymeric nanoparticles (RA-NPs) modulates the murine microglial response towards an anti-inflammatory and neuroprotective phenotype (M2-like) in organotypic hippocampal slice cultures [ 143 ]. Recently, the intravenous administration of RA-NPs was shown to prevent ischemic injury in the immature brains of 2-day-old mice, demonstrating the role of RA in the control of neuroinflammation [ 144 ].…”
Section: Immunomodulatory Effect Of Ra During Inflammatory Processmentioning
confidence: 99%
“…[9] There is an abundance of experimental and clinical research supporting ROS as a promising therapeutic target for acute ischemic stroke. [16][17][18] For example, Liu and colleagues have demonstrated that melanin NPs (MeNPs) scavenge multiple reactive oxygen and nitrogen species (RONS), suppress RONS-induced inflammation, and are neuroprotective in vitro. On the other hand, several promising antioxidant nanoparticles (NPs) have been developed in recent years, with the perspective capacity of suppressing ROS-induced damage following ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral ischemia also activates important delayed endogenous repair processes such as BBB repair, neurogenesis, and angiogenesis that are important for functional recovery and patient rehabilitation in clinical settings, and evidence suggests that the sub-acute phase of inflammation plays a key role in this process. The anti-inflammatory phenotype of microglia exhibits neuroprotective and anti-inflammatory effects during the delayed phase of post-stroke inflammation, producing anti- inflammatory cytokines such as IL-10, transforming growth factor (TGF)-β, IL-4, and IL-13, as well as scavenge receptors, contributing to inhibiting inflammation and promoting tissue repair mechanisms ( 28 ). Of those, neurogenesis—known to take place in the sub granular zone of the dentate gyrus of the hippocampus and in the sub ventricular zone adjacent to the third ventricle ( 29 )—is increased following experimental stroke ( 30 ), and is regulated by inflammatory mediators expressed during the acute phase of stroke ( 31 ).…”
Section: Inflammation In Strokementioning
confidence: 99%
“…Biocompatibility was assessed in vitro and in vivo , with NPs demonstrating no obvious toxicity. Another type of NPs, retinoic acid-loaded polymeric NPs (RA-NP) have been developed to modulate microglial response toward an anti-inflammatory and somehow neuroprotective phenotype ( 28 ). RA-NP were internalized by murine N9 microglial cell line and inhibited LPS-induced iNOS expression and NO release, whilst promoting arginase-1 and IL-4 production.…”
Section: Anti-inflammatory Strategies In Regenerative Medicinementioning
confidence: 99%